The Secret to Successful Investment in Children's Education: Active Parental Involvement in Education - Andy Prasetyo Wati; Jefry Aulia Martha; Buyung Adi Dharma; Annisya' Annisya'; Nur Anita Yunikawati; Lifa Farida Panduwinata (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
The problem of this study is more emphasized on how much influence parents have in educating children to achieve success. The purpose of this article focuses on how to know and understand the impact of factors owned by parents, such as parents' socio-economic status and children's plans through education that parents and rationalization have made of the value of education can affect the success of children's education. The population and sample of the study were parents who currently have school-age children in grade XII in Malang City, with a total population of 19,501 respondents and a total sample of 377 respondents. The sampling technique used Cochran, data collection techniques through questionnaires with a 7-point Likert scale, and analysis techniques using multiple linear regression. The results showed that both simultaneously and partially, it is known that EP, EC, and VR can influence the success of children's education investment. Thus, further action is needed from the parents and the government in this regard to support the implementation of optimal educational investment to increase the child's potential.